2017
DOI: 10.20944/preprints201704.0154.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water Bridging Dynamics of Polymerase Chain Reaction in the Gauge Theory Paradigm of Quantum Fields

Abstract: Abstract:We discuss the role of water bridging the DNA-enzyme interaction by resorting to recent results showing that London dispersion forces between delocalized electrons of base pairs of DNA are responsible for the formation of dipole modes that can be recognized by Taq polymerase. We describe the dynamical origin of the high efficiency and precise targeting of Taq activity in PCR. The spatiotemporal distribution of interaction couplings, frequencies, amplitudes, and phase modulations comprise a pattern of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…After recording, DNA information could be transmitted to water and carried in water nanostructures. Furthermore, the same authors reported that classical polymerase chain reaction could be performed by using specific DNA information stored in these nanostructures [ 37 ]. Montagnier’s hypothesis of water nanostructures is clearly in favour of a role of water as a carrier of molecular information.…”
Section: Discussionmentioning
confidence: 99%
“…After recording, DNA information could be transmitted to water and carried in water nanostructures. Furthermore, the same authors reported that classical polymerase chain reaction could be performed by using specific DNA information stored in these nanostructures [ 37 ]. Montagnier’s hypothesis of water nanostructures is clearly in favour of a role of water as a carrier of molecular information.…”
Section: Discussionmentioning
confidence: 99%
“…The second conclusive point to emphasize is that this intentional approach to cognitive neurosciences based on the quantum entanglement brain-environment acquires an immediate logical and computational relevance if we consider that the same coalgebraic modeling [26] holds, both for "dissipative" QFT systems in the foundations of condensed matter physics [25]-biological [27][28][29][30] as well neural systems included [19,20]-and for Saul Kripke's modal relational semantics in theoretical computer science [31][32][33][34] 3 . The modal calculus is, indeed, the proper logic of formal ontology, but 3 (Co-)Algebraic coproducts, indeed, are effectively sums.…”
Section: Conclusion: the Necessary Path Toward An Ethically Accountable Aimentioning
confidence: 99%
“…A ground wire is used to link the transmitter and receiver coil connecting the outside end of the secondary coil. The primary coil is printed under the printed circuit board with the same width and space, but shorter length [8] and connected directly to the DDS (Direct Digital Synthesizer) generator, whose output impedance is usually under 10 Ohms. When the two coils meet the condition of same frequency, same wave shape and opposite phase shift, self-resonance of the whole system will be generated.…”
Section: Electromagnetically Resonance (Emr) Apparatusmentioning
confidence: 99%